Pemanfaatan Data Oriented Technology Stack dalam Game Engine Unity dan Teknologi Klasik Unity untuk Membuat Permainan Danmaku - Tantyo N. T.; Med Irzal; Lipur Sugiyanta (Universitas Negeri Jakarta, 2023)
Video games are relatively resource-intensive. Unlike most common apps, they require additional quality of their resources such as bigger RAM and faster processing speed due to the nature of unpredictability. Even now, one could say that despite the advancement in hardware technologies; a number of video games still demand better resources. To aid this issue, Unity Technologies has introduced a new technology called Data Oriented Technology Stack for their game engine; or DOTS. The DOTS technology is based on the Entity Component System architecture which is an adaptation of the data-oriented paradigm for engineering a software program or for a solution. But as of the time of writing this, the technology isn’t ready yet and considered unstable; so a game developer that wishes to use DOTS still need to use the classic technology of the engine. To display the usability and a degree of potential from Unity’s DOTS technology, this thesis will present a danmaku game development using both DOTS and the classic MonoBehaviour technology.